2020
DOI: 10.14214/sf.10276
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Scots pine half-sib families to <i>Heterobasidion annosum</i> in progeny field trials

Abstract: Five Scots pine ( L.) progeny field trials, each established in different Lithuanian regions of provenance in 1983, were studied. Each progeny field trial consists of 140 half-sib families from seven populations (20 families from each population). The evaluation was carried out in 2012 and 2018 to assess the families resistance to (Fr.) Bref. An index of resistance in the infected plots was calculated. To verify the accuracy of the method, total phenolic compounds (TPC) was chosen as key parameter to compare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
2
0
2
Order By: Relevance
“…Narrow-sense heritability estimates of 0.38–0.75 for Dothistroma needle blight severity differed between half-siblings and full-siblings (Perry et al, 2016 ). A narrow-sense heritability of 0.37 for root rot resistance was higher than those for many growth traits (Rieksts-Riekstinš et al, 2020 ), and the high estimates were documented to be valuable for breeding (Marčiulynas et al, 2020 ). A positive relationship between height and lesion area indicated that seedlings of larger size were much more susceptible to H. annosum .…”
Section: Discussionmentioning
confidence: 99%
“…Narrow-sense heritability estimates of 0.38–0.75 for Dothistroma needle blight severity differed between half-siblings and full-siblings (Perry et al, 2016 ). A narrow-sense heritability of 0.37 for root rot resistance was higher than those for many growth traits (Rieksts-Riekstinš et al, 2020 ), and the high estimates were documented to be valuable for breeding (Marčiulynas et al, 2020 ). A positive relationship between height and lesion area indicated that seedlings of larger size were much more susceptible to H. annosum .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, planting less-susceptible tree species or genotypes in stands already infected by Heterobasidion spp. is also recommended (Marčiulynas et al, 2020).…”
Section: Chemical Treatmentmentioning
confidence: 99%
“…Польські вчені (Napierała-Filipiak & Filipiak 2011 довели, що збереженість інокульованих Heterobasidion annosum s. l потомств сосни звичайної (Pinus sylvestris L.), вирощених із насіння «умовно стійких» дерев, є кращою, ніж потомств, вирощених із елітного насіння, зібраного на клонових насінних плантаціях (КНП). У Литві порівняли за стійкістю природне поновлення у старих осередках кореневої гнилі та потомства плюсових дерев і виявили перевагу перших (Marčiulynas et al 2020). У наших попередніх дослідженнях виявлено, що насіння стійких дерев, на відміну від «хворих», характеризується вищими енергією проростання та схожістю, але поступається інтенсивністю росту проростків (Dyshko 2021).…”
unclassified
“…У наших попередніх дослідженнях виявлено, що насіння стійких дерев, на відміну від «хворих», характеризується вищими енергією проростання та схожістю, але поступається інтенсивністю росту проростків (Dyshko 2021). Незважаючи на результати досліджень, стратегія тотального відбору всіх життєздатних рослин в осередках кореневої губки, вчені не підтримують, оскільки потомства таких дерев суттєво різняться за стійкістю до кореневих гнилей (Marčiulynas et al 2020). Зважаючи на це, дослідження особливостей росту й розвитку потомств дерев із підвищеною стійкістю є надзвичайно важливим.…”
unclassified